Field evaluation of Trichoderma harzianum, Pochonia chlamydosporia and Pasteuria penetrans in a root knot nematode infested black pepper (Piper nigrum L.) garden in India - J. Eapen, Santhosh; Beena, B.; Ramana, K.V. (Journal of Plantation Crops, 2009)
Two fungal bioagents (Trichoderma harzianum and Pochonia chlamydosporia) and a bacterial endoparasite (Pasteuria penetrans) were evaluated for biological control of nematodes in a black pepper garden in Waynad District of Kerala, India for five years (1998-2001) in a randomized block design with six treatments replicated thrice. The yellowing of vines in the experimental plot has decreased in all the treatments after the first year onwards. After four years, the lowest incidence of yellowing (15.25 %) was noticed in plots treated with phorate followed by plots treated with P. chlamydosporia (20.78 %) and P. penetrans (24.13 %). The highest mean yield (1.83 kg vine-1) was obtained in P. chlamydosporia treated plots followed by combined application of phorate and potassium phosphonate (1.50 kg vine-1). The lowest mean population of root-knot nematodes in black pepper roots was observed in phorate + potassium phosphonate treated plants followed by P. penetrans treated plants. The final nematode level was the lowest in P. chlamydosporia treated plots. The study has clearly proved the efficacy of these bioagents, especially P. chlamydosporia for managing root knot nematodes in black pepper gardens.